Ceramic enhancement process based on nano-material and preparation method of nano-material enhanced ceramic
By using modified nanomaterials in ceramic materials and adopting optimized dispersion and mixing processes, the problems of poor dispersion, high cost and processing complexity of nanomaterials in ceramic enhancement are solved, and high performance and environmentally friendly production of ceramic materials are achieved.
Patent Information
- Application Number
- CN202411138873.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-02-07
AI Technical Summary
In the existing ceramic reinforcement technology, the nanomaterials have poor dispersion, high cost, complex processing technology and insufficient long-term stability.
By selecting the appropriate nanomaterial and performing surface modification treatment, ultrasonic dispersion process and wet mixing process, combining hot press forming and sintering processes, the pretreatment and mixing process of ceramic matrix materials is optimized to ensure uniform dispersion of nanomaterials and ceramics. High density of the material.
It significantly improves the strength, hardness, wear resistance and thermal stability of ceramic materials, reduces the preparation cost, reduces the impact on the environment, and improves the safety and sustainability of the production process.
Smart Images

Figure CN119390462A_ABST
Abstract
Description
Technical Field
[0001] This technical solution involves a ceramic material reinforcement process, in particular a ceramic reinforcement process based on nanomaterials and a method for preparing nanomaterial-reinforced ceramics. The solution aims to solve the problems of poor dispersion of nanomaterials, high cost, complex processing technology, and long-term stability of nanomaterials in the prior art. Background Art
[0002] In the existing ceramic reinforcement technology, nanomaterials are widely used as reinforcing agents in ceramic matrices to improve their mechanical properties, wear resistance and thermal stability. Commonly used nano-reinforced materials include nano-silicon (SiO2), nano-aluminum (Al2O3), nano-carbon materials (such as carbon nanotubes, graphene), etc. These nanomaterials are usually uniformly dispersed in the ceramic matrix through wet mixing, dry mixing, sol-gel method or chemical vapor deposition (CVD) and other processes, and high-performance ceramic materials are prepared by hot pressing or sintering. These ceramic materials have been widely used in aerospace, automotive industry, electronic components, tool manufacturing and other fields, especially in applications with high strength, high temperature and high wear resistance requirements, nano-reinforced ceramics show excellent performance. Although the prior art has made significant progress in nanomaterial-reinforced ceramics, there are still some objective shortcomings that need to be solved. First, the uniform dispersion of nanomaterials in the ceramic matrix is poor, and particles are prone to agglomeration or precipitation, resulting in uneven material properties, which in turn affects its overall mechanical properties. Secondly, the preparation and processing of nanomaterials are complex and costly, which limits their application in large-scale production. In addition, the insufficient interfacial bonding between nanomaterials and ceramic matrix also affects the reinforcement effect, resulting in a decrease in the stability of the material in long-term use. Finally, nanomaterials may produce byproducts that are harmful to the environment and health during production and processing, increasing the difficulty of environmental protection and safety management.
[0003] In view of the shortcomings of the existing technology, this technical solution proposes a new ceramic reinforcement process and preparation method. By introducing modified nanomaterials and optimizing the dispersion process, the strength, hardness, wear resistance and thermal stability of ceramics are significantly improved. By further optimizing the production process and material selection, the preparation cost is reduced, making the ceramic reinforcement process based on nanomaterials more economical. Due to the adoption of environmental protection measures, this technical solution can reduce the impact on the environment and improve the safety and sustainability of the production process. Summary of the invention
[0004] In view of the shortcomings of the existing technology, this specification provides a new ceramic reinforcement process and preparation method, which significantly improves the performance of ceramics by introducing modified nanomaterials and optimizing the dispersion process, and can also reduce the preparation cost by optimizing the production process and material selection. Finally, environmental protection measures are taken to improve the safety and sustainability of the production process.
[0005] The embodiments of this specification provide the following technical solutions:
[0006] A nanomaterial-based ceramic reinforcement process and a nanomaterial-reinforced ceramic preparation method, comprising:
[0007] Step 1, selecting nanomaterials and performing surface modification treatment on them: in a protective atmosphere, the nanomaterials are mixed with a modifier, and reacted at 750-1000° C. in a CVD device to obtain modified nanomaterials.
[0008] Furthermore, the nanomaterial includes one or more of nano boron nitride (BN), nano zirconium oxide (ZrO2) and nano silicon carbide (SiC); the protective atmosphere includes but is not limited to nitrogen and hydrogen; the modifier includes but is not limited to aminosilane, aminoethyl sulfonate, silicon nitride coating, etc.
[0009] Step 2, weigh the modified nano material 10-20 gram of preparation in step 1, be scattered in the deionized water or ethanol solution of 200-1000mL, then, add appropriate surfactant, such as polyvinyl pyrrolidone (PVP), its addition is 0.5-2% (i.e. 0.05-0.4 gram) of nano material quality, obtains dispersion liquid. Deionized water or ethanol solution described here, the principle of selection is to determine which solvent to use according to the chemical characteristic of nano material, such as nano SiC can use ethanol, and nano ZrO2 is suitable for using deionized water. Continue to place dispersion solution in ultrasonic dispersion instrument and carry out dispersion treatment. After the dispersion treatment, the dispersion liquid is centrifuged, and the supernatant after centrifugation is dried to obtain nano material powder.
[0010] Furthermore, the process of dispersing in the ultrasonic disperser is to place the prepared dispersion solution in the ultrasonic disperser and disperse it using ultrasound with a frequency of 20-40kHz. The dispersion time is controlled to be 30-60 minutes. Under the action of ultrasound, the cavitation generated in the liquid will form a large number of tiny bubbles. The shock waves generated when these bubbles burst instantly can effectively destroy the agglomeration of nanoparticles, so that they are evenly distributed in the solution.
[0011] Furthermore, the centrifugal treatment after the ultrasonic dispersion treatment is performed to remove any remaining larger particles or impurities. The centrifugal parameters selected during the centrifugal treatment are 3000-5000 rpm and the time is 10-15 minutes. After centrifugation, the supernatant is dried at a temperature of 60-80°C.
[0012] Step 3. In order to ensure that the ceramic matrix material has a uniform particle size distribution and excellent mixing performance before mixing with the nanomaterial, the technical solution pre-treats the ceramic matrix material. The pretreatment process includes crushing, screening, and homogenization treatment with a mechanical mixer to ensure that the particle size distribution of the pre-treated material is uniform. The block or large-particle ceramic matrix material is preliminarily crushed, and the particle size of the preliminarily crushed ceramic matrix material powder is controlled within the range of 2-5μm using a ball mill or grinder. The ceramic matrix material powder after preliminary crushing may contain a small amount of oversized or undersized particles, so screening treatment is continued. The screened ceramic matrix material powder is homogenized by a mechanical mixer to ensure the uniformity of the particle distribution.
[0013] Furthermore, the screening process uses 200 mesh (75 μm) and 325 mesh (45 μm) sieves to classify the ceramic matrix material powder, and takes the ceramic matrix material powder between 200 mesh (75 μm) and 325 mesh (45 μm).
[0014] Furthermore, in the homogenization process, the rotation speed of the mechanical mixer is set between 100-300 rpm, and the mixing time is 30-60 minutes.
[0015] Step 4, in order to achieve uniform dispersion of the modified nanomaterial and the pretreated ceramic matrix material, the present technical solution adopts a wet mixing process. The purpose of the wet mixing process is to mix the two materials in a liquid medium and make the nanomaterial uniformly distributed in the ceramic matrix through the efficient stirring action of the ball mill. Weigh the modified nanomaterial and the pretreated ceramic matrix material, mix them in a mass ratio of 1:9 to 1:4, and add ethanol as a dispersion medium, and control the liquid-solid ratio between 3:1 and 5:1, that is, the amount of ethanol added is 3 to 5 times the mass of the ceramic matrix material, and then ball milling is performed to obtain a mixed slurry. Continue to pour the prepared mixed slurry into the ball milling tank of the planetary ball mill, add an appropriate amount of zirconia balls as grinding media for ball milling mixing. Here, the amount of grinding media added is controlled to be 50-70% of the solid mass, the speed of the ball mill is set to 400-600rpm, and the mixing time is 2-4 hours. After the ball milling process is completed, a small amount of slurry is taken out for testing to observe the particle distribution. The qualified slurry needs to be spray-dried or vacuum-freeze-dried to remove the liquid part to obtain a solid composite powder.
[0016] Furthermore, in the process of preparing the mixed slurry by ball milling, the speed of the ball mill is controlled between 200-300 rpm, and the ball milling time is 2-4 hours. To further improve the uniformity, a small amount of solvent, such as ethanol or water, can be added during the mixing process if necessary to reduce the friction of the powder and ensure the uniform dispersion of the nanomaterial in the ceramic matrix.
[0017] Furthermore, the particle distribution is observed by using a dynamic light scattering (DLS) or a laser particle size analyzer to measure the particle distribution in the mixture. Ideally, the nanomaterial should be evenly dispersed in the ceramic matrix without obvious agglomeration. The Zeta potential of the slurry is controlled to be above ±30 mV to ensure good stability.
[0018] Step 5: Select an appropriate hot pressing mold to press the composite ceramic powder obtained in step 4 into a blank based on the hot pressing process to obtain a hot pressed ceramic blank. The inner wall of the hot pressing mold needs to be precisely machined and coated with a release agent (such as graphite or boron nitride coating) to reduce friction and adhesion during the molding process, thereby ensuring the surface quality of the ceramic blank and smooth demolding.
[0019] Furthermore, in the hot pressing process, the solid composite powder obtained in step 4 needs to be uniformly loaded into the mold. During the loading process, it is necessary to ensure that the density of the solid composite powder is uniformly distributed to avoid the generation of pores or cracks. To improve the loading effect, a small amount of pre-pressure can be applied during the loading process, and the pressure range is between 5-10MPa to preliminarily densify the solid composite powder.
[0020] Furthermore, in the hot pressing forming process, the pressure range of hot pressing forming is 20-50 MPa, the temperature range is 1200-1600° C., and the holding time is set to 30-60 minutes.
[0021] Furthermore, in the hot pressing process, the heating rate is set to 10-20°C / minute. After reaching the target temperature, the constant temperature and pressure are maintained for 30-60 minutes to fully combine and densify the ceramic particles and nanomaterials inside the material. After the insulation is completed, the temperature is slowly lowered, and the cooling rate is controlled at 5-10°C / minute. During the cooling process, the pressure is gradually reduced until it reaches normal pressure. After cooling to room temperature, the mold is removed and the formed ceramic composite material is taken out. The product is preliminarily inspected to ensure that there are no obvious defects or cracks on the surface.
[0022] Step 6: Place the hot-pressed ceramic body in a sintering furnace for sintering, set the sintering temperature to 1600-1800° C., and the sintering time to 2-4 hours. After sintering, cool it naturally and slowly to room temperature to obtain nano-material reinforced ceramics.
[0023] Furthermore, the argon protective atmosphere is continuously maintained during the natural cooling process, and the argon flow rate is controlled between 10-20 L / min, in order to ensure that the ceramic material does not undergo oxidation reaction during the cooling process.
[0024] Compared with the prior art, the at least one technical solution adopted in the embodiments of this specification can achieve the following beneficial effects:
[0025] The technical solution provided in this specification significantly improves the strength and hardness of the ceramic matrix by using nanomaterials (such as nano boron nitride, nano zirconium oxide or nano silicon carbide) for reinforcement. The uniform dispersion of nanomaterials in the ceramic matrix effectively improves the flexural strength and compressive strength of the material. For example, experimental results show that the flexural strength of zirconium oxide (ZrO2) composite materials reinforced with nano silicon carbide (SiC) reaches 520MPa, which is 25% higher than that of traditional ceramic materials. This significant improvement in mechanical properties enables the material to have better service life and reliability under high load conditions.
[0026] The technical solution provided in this specification significantly improves the wear resistance and corrosion resistance of the material by applying a high-hardness nano-coating (such as SiC) on the surface of the ceramic material and performing subsequent polishing. The coating treatment and polishing make the material surface smoother and reduce the friction coefficient, thereby reducing the occurrence of wear and corrosion. In the experiment, the ceramic material coated with the SiC layer showed a 20% improvement in wear resistance, making it perform better in harsh operating environments.
[0027] The technical solution provided in this specification has significantly improved the density of the material by optimizing the hot pressing and sintering processes. During the sintering process, reasonable temperature, pressure and holding time ensure the full densification of the material, reduce the porosity, and increase the relative density of the material (>99% theoretical density). High-density ceramic materials not only have better structural stability, but also can effectively resist the influence of harsh environments such as high temperature and chemical erosion.
[0028] The technical solution provided in this specification uses argon protective atmosphere for sintering, which avoids the oxidation reaction of ceramic materials at high temperatures, making the material have excellent thermal stability and chemical stability. The coating treatment of ceramic materials further improves the material's antioxidant ability and ensures long-term stability in high temperature and strong corrosive environments.
[0029] In the technical solution provided in this specification, due to the introduction of nanomaterials, ceramic composite materials have multiple functionalities, such as high strength, high temperature resistance, wear resistance, etc., making them have wide application potential in high-tech fields such as aerospace, automotive industry, electronic devices, and medical equipment. Especially in high temperature, high pressure and corrosive environments, this high-performance ceramic material shows excellent application prospects.
[0030] The surface finish of the ceramic material after polishing in the technical solution provided in this specification is significantly improved, and the roughness is reduced to Ra = 0.1μm, which improves the aesthetics and surface quality of the material. In addition, good surface properties make the material more convenient in subsequent processing and application, which is conducive to improving the processing efficiency and service life of the finished product.
[0031] In summary, compared with the existing technology, the technical solution provided in this specification has stronger mechanical properties, better wear resistance and corrosion resistance, higher density, better surface properties and processability, higher functional application potential, wider applicability, and significant progressive significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the process flow chart in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Figure 1 It is a schematic diagram of the preparation process of the nano material ceramic reinforcement process involved in the embodiment of the present invention; Figure 2 is a schematic diagram of the nanomaterial selection and surface modification process involved in the embodiments of the present invention; Figure 3 is a schematic diagram of the dispersibility analysis of nanomaterials involved in the embodiments of the present invention; Figure 4 It is a schematic diagram of the hot pressing forming process steps involved in the embodiment of the present invention. DETAILED DESCRIPTION
[0033] The embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0034] The following describes the implementation methods of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The present application can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application. It should be noted that, in the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present application.
[0035] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein can be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present application, it should be understood by those skilled in the art that an aspect described herein can be implemented independently of any other aspect, and two or more of these aspects can be combined in various ways. For example, any number and aspect described herein can be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein can be used to implement this device and / or practice this method.
[0036] It should also be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present application. The drawings only show components related to the present application rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0037] Additionally, in the following description, specific details are provided to facilitate a thorough understanding of the examples. However, it will be understood by those skilled in the art that the aspects described may be practiced without these specific details.
[0038] In the prior art, nanomaterials are mixed with ceramic raw materials, and then wet grinding is used to evenly distribute the nanoparticles. Common grinding media include ball mills, planetary mills, etc. Nanomaterials are used for ceramic reinforcement and face problems such as poor uniform dispersion, high cost, complex processing technology, and poor long-term stability. Insufficient uniform dispersion of nanomaterials will lead to unstable performance, while high cost and complex process limit the wide range of practical applications.
[0039] In response to the above problems, the embodiments of the present application provide a new ceramic reinforcement process and preparation method, which realizes the preparation of nano-ceramic-based materials with better performance, environmental friendliness and higher application value through the selection and modification of nano-materials, uniform dispersion of nano-materials, wet mixing, hot pressing and post-processing.
[0040] This application mainly includes the following steps:
[0041] Step 1, selecting nanomaterials and performing surface modification treatment on them: in a protective atmosphere, the nanomaterials are mixed with a modifier, and reacted at 750-1000° C. in a CVD device to obtain modified nanomaterials.
[0042] Specifically, the nanomaterial refers to one or more of nano boron nitride (BN), nano zirconium oxide (ZrO2) and nano silicon carbide (SiC); the protective atmosphere includes but is not limited to nitrogen and hydrogen; the modifier includes but is not limited to aminosilane, aminoethyl sulfonate, silicon nitride coating, etc.
[0043] Step 2, weigh 10-20 grams of the modified nano material prepared in step 1, disperse it in 200-1000mL of deionized water or ethanol solution, then add an appropriate amount of surfactant, such as polyvinyl pyrrolidone (PVP), the amount of which is 0.5-2% (i.e. 0.05-0.4 grams) of the mass of the nano material to obtain a dispersion. Continue to place the dispersion solution in an ultrasonic disperser for dispersion treatment. After the dispersion treatment, the dispersion is centrifuged, and the supernatant after centrifugation is dried to obtain a nano material powder.
[0044] The process of dispersing in an ultrasonic disperser is to place the prepared dispersion solution in an ultrasonic disperser and disperse it using ultrasonic waves with a frequency of 20-40 kHz. The dispersion time is controlled within 30-60 minutes.
[0045] The purpose of the centrifugal treatment after the ultrasonic dispersion treatment is to remove the larger particles or impurities that may remain. The centrifugal parameters selected during the centrifugal treatment are 3000-5000rpm and the time is 10-15 minutes. After centrifugation, the supernatant is taken for drying at a temperature between 60-80°C.
[0046] Step 3. In order to ensure that the ceramic matrix material has a uniform particle size distribution and excellent mixing performance before mixing with the nanomaterial, the technical solution pre-treats the ceramic matrix material. The pretreatment process includes crushing, screening, and homogenization treatment with a mechanical mixer to ensure that the particle size distribution of the pre-treated material is uniform. The block or large-particle ceramic matrix material is preliminarily crushed, and the particle size of the preliminarily crushed ceramic matrix material powder is controlled within the range of 2-5μm using a ball mill or grinder. The ceramic matrix material powder after preliminary crushing may contain a small amount of oversized or undersized particles, so screening treatment is continued. The screened ceramic matrix material powder is homogenized by a mechanical mixer to ensure the uniformity of the particle distribution.
[0047] Specifically, the screening operation is to use 200 mesh (75 μm) and 325 mesh (45 μm) sieves to classify the ceramic matrix material powder, and then take the ceramic matrix material powder between 200 mesh (75 μm) and 325 mesh (45 μm).
[0048] Specifically, in the homogenization process, the rotation speed of the mechanical mixer is set between 100-300 rpm, and the mixing time is 30-60 minutes.
[0049] Step 4, in order to achieve uniform dispersion of the modified nanomaterial and the pretreated ceramic matrix material, the present technical solution adopts a wet mixing process. The purpose of the wet mixing process is to mix the two materials in a liquid medium and make the nanomaterial uniformly distributed in the ceramic matrix through the efficient stirring action of the ball mill. Weigh the modified nanomaterial and the pretreated ceramic matrix material, mix them in a mass ratio of 1:9 to 1:4, and add ethanol as a dispersion medium, and control the liquid-solid ratio between 3:1 and 5:1, that is, the amount of ethanol added is 3 to 5 times the mass of the ceramic matrix material, and then ball milling is performed to obtain a mixed slurry. Continue to pour the prepared mixed slurry into the ball milling tank of the planetary ball mill, add an appropriate amount of zirconia balls as grinding media for ball milling mixing. Here, the amount of grinding media added is controlled to be 50-70% of the solid mass, the speed of the ball mill is set to 400-600rpm, and the mixing time is 2-4 hours. After the ball milling process is completed, a small amount of slurry is taken out for testing to observe the particle distribution. The qualified slurry needs to be spray-dried or vacuum-freeze-dried to remove the liquid part to obtain a solid composite powder.
[0050] Specifically, in the process of preparing the mixed slurry by ball milling, the speed of the ball mill is controlled between 200-300 rpm, and the ball milling time is 2-4 hours. To further improve the uniformity, a small amount of solvent, such as ethanol or water, can be added during the mixing process if necessary to reduce the friction of the powder and ensure the uniform dispersion of the nanomaterial in the ceramic matrix.
[0051] Specifically, the particle distribution is observed by using a dynamic light scattering (DLS) or a laser particle size analyzer to measure the particle distribution in the mixture. Ideally, the nanomaterial should be evenly dispersed in the ceramic matrix without obvious agglomeration. Generally, the Zeta potential of the slurry should be controlled above ±30mV to ensure good stability.
[0052] Step 5: Select an appropriate hot pressing mold to press the composite ceramic powder obtained in step 4 into a blank based on the hot pressing process to obtain a hot pressed ceramic blank. The inner wall of the hot pressing mold needs to be precisely machined and coated with a release agent (such as graphite or boron nitride coating) to reduce friction and adhesion during the molding process, thereby ensuring the surface quality of the ceramic blank and smooth demolding.
[0053] Specifically, in the hot pressing process, the solid composite powder obtained in step 4 needs to be uniformly loaded into the mold. During the loading process, it is necessary to ensure that the density of the solid composite powder is uniformly distributed to avoid the generation of pores or cracks. To improve the loading effect, a small amount of pre-pressure can be applied during the loading process, and the pressure range is between 5-10MPa to preliminarily densify the solid composite powder.
[0054] Specifically, in the hot pressing process, the pressure range of hot pressing is 20-50 MPa, the temperature range is 1200-1600° C., and the holding time is set to 30-60 minutes.
[0055] Specifically, in the hot pressing process, the heating rate is set at 10-20°C / minute. After reaching the target temperature, the constant temperature and pressure are maintained for 30-60 minutes to fully combine and densify the ceramic particles and nanomaterials inside the material. After the insulation is completed, the temperature is slowly lowered, and the cooling rate is controlled at 5-10°C / minute. During the cooling process, the pressure is gradually reduced until it reaches normal pressure. After cooling to room temperature, the mold is removed and the formed ceramic composite material is taken out. A preliminary inspection is carried out on the product to ensure that there are no obvious defects or cracks on the surface.
[0056] Step 6: Place the hot-pressed ceramic body in a sintering furnace for sintering, set the sintering temperature to 1600-1800°C, and the sintering time to 2-4 hours. After sintering, cool it down to room temperature naturally to prevent cracks or deformation of the material due to rapid cooling, and finally obtain nano-material reinforced ceramics.
[0057] During the natural cooling process, the argon protective atmosphere is continuously maintained, and the argon flow rate is controlled between 10-20 L / min.
[0058] The following is a description of a nanomaterial-based ceramic reinforcement process and a method for preparing nanomaterial-reinforced ceramics, as well as testing of nanomaterials to observe the performance of prepared samples, using specific embodiments as examples.
[0059] Step 6: After hot pressing, place the ceramic body in a sintering furnace. After sintering, slowly cool it down to room temperature. Maintain an argon protective atmosphere during the cooling process.
[0060] The sintering temperature is 1600-1800°C and the sintering time is 2-4 hours.
[0061] The argon gas flow rate is controlled between 10-20 L / min.
[0062] Embodiment 1,
[0063] Step 101: In a protective atmosphere of nitrogen and hydrogen, nano-BN is mixed with aminosilane (R-Si(OR')3), and reacted at 750° C. by a CVD process to form a siloxane coating on the surface of the nano-BN.
[0064] Step 102, weigh 15g of the surface-modified nano BN in Example 101, disperse it in 600mL of deionized water, and add an appropriate amount of surfactant PVP. Place the prepared dispersion solution in an ultrasonic disperser and disperse it using ultrasound with a frequency of 30kHz. The dispersion time is 45 minutes. After the dispersion treatment, the dispersion is centrifuged at 4000rpm for 15 minutes, and the supernatant after centrifugation is dried at 70°C to obtain nanomaterial powder;
[0065] Step 103, preliminarily crush the blocky or large-particle ceramic matrix material ZrO2, and use a ball mill to control its particle size within the range of 2-5μm. Screening uses 200 mesh (75μm) and 325 mesh (45μm) sieves to classify the powder. The screened ceramic matrix material needs to be homogenized by a mechanical mixer to ensure the uniformity of particle distribution. The speed of the mechanical mixer is set at 250rpm, and the mixing time is 50 minutes.
[0066] Step 104, weigh the modified nano material nano boron nitride and the pretreated ceramic matrix material zirconium oxide, and add them in a ratio of 1:4, that is, 20 grams of nano boron nitride and 80 grams of zirconium oxide. Add ethanol as a dispersion medium, and the amount of ethanol added is 3 times the mass of the ceramic matrix material, that is, 240 grams. Pour the prepared mixed slurry into the ball mill of the planetary ball mill, and add 170 grams of zirconium oxide balls as grinding media. Set the speed of the ball mill to 500rpm and the mixing time to 4 hours. Remove the liquid part by spray drying or vacuum freeze drying to obtain a solid composite powder. During the drying process, control the temperature at 70°C.
[0067] Step 105, select a cemented carbide mold. The inner wall of the mold is coated with a boron nitride coating release agent. A small amount of pre-pressure of 10MPa is applied during the filling process. The hot pressing pressure is 20Mpa, the temperature is 1300℃, and the holding time is set to 50 minutes. The heating rate is set to 15℃ / minute. After the holding is completed, the temperature is slowly cooled to room temperature, and the cooling rate is controlled at 10℃ / minute.
[0068] Step 106: After cooling to room temperature, the sintered ceramic material is polished using diamond polishing paste by gradually reducing the sandpaper particle size until the surface reaches the desired smoothness.
[0069] Before and after surface modification, nano-BN was characterized by transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). The modified nano-BN surface has a uniform siloxane coating, and the Zeta potential increases to ±40mV, which significantly improves the dispersibility. Raman spectroscopy analysis shows that the distribution uniformity of the modified BN particles in the ceramic matrix is improved by 25%. The toughness of the ceramic matrix material reinforced with nano-boron nitride is improved by 18%.
[0070] Embodiment 2,
[0071] Step 201, using CVD process to modify the surface of nano ZrO2 with a particle size of 50 nm, using aminoethyl sulfonate as a modifier, reacting at 850° C., so that a nitrogen-containing group coating is formed on the surface of the nano ZrO2.
[0072] Step 202, weigh 20g of the surface-modified nano ZrO2 in Example 201, disperse it in 1000mL of deionized water, and add an appropriate amount of surfactant PVP. Place the prepared dispersion solution in an ultrasonic disperser and disperse it using ultrasound with a frequency of 40kHz. The dispersion time is 60 minutes. After the dispersion treatment, the dispersion is centrifuged at 4000rpm for 15 minutes, and the supernatant after centrifugation is dried at 70°C to obtain nano material powder;
[0073] Step 203, preliminarily crush the blocky or large-particle ceramic matrix material Al2O3, and use a ball mill to control its particle size within the range of 2-5μm. Screening uses 200 mesh (75μm) and 325 mesh (45μm) sieves to classify the powder. The screened ceramic matrix material needs to be homogenized by a mechanical mixer to ensure the uniformity of particle distribution. The speed of the mechanical mixer is set at 250rpm, and the mixing time is 50 minutes.
[0074] Step 204, weigh the modified nano material nano zirconium oxide and the pretreated ceramic matrix material alumina, and add them in a ratio of 1:7, that is, 20 grams of nano zirconium oxide and 140 grams of zirconium oxide. Add ethanol as a dispersion medium, and the amount of ethanol added is 4 times the mass of the ceramic matrix material, that is, 560 grams. Pour the prepared mixed slurry into the ball mill of the planetary ball mill, and add 360 grams of zirconium oxide balls as grinding media. Set the speed of the ball mill to 600rpm and the mixing time to 4 hours. Remove the liquid part by spray drying or vacuum freeze drying to obtain a solid composite powder. During the drying process, control the temperature at 70°C.
[0075] Step 205, select a cemented carbide mold. The inner wall of the mold is coated with a boron nitride coating release agent. A small amount of pre-pressure of 10MPa is applied during the filling process. The hot pressing pressure is 20Mpa, the temperature is 1300°C, and the holding time is set to 50 minutes. The heating rate is set to 15°C / minute. After the holding is completed, the temperature is slowly cooled to room temperature, and the cooling rate is controlled at 10°C / minute.
[0076] Step 206: After cooling to room temperature, the sintered ceramic material is polished using diamond polishing paste by gradually reducing the sandpaper particle size until the surface reaches the desired smoothness.
[0077] XPS characterization of the modified nano ZrO2 showed that the nitrogen group content introduced on the surface reached 5.2at%. Raman spectroscopy analysis showed that the bonding force between ZrO2 particles and the ceramic matrix was enhanced by 30%, and the bending strength was increased by 15%. In addition, the modified ZrO2 particles showed better thermal shock resistance after heat treatment. The fracture of the ceramic material reinforced with nano zirconium oxide was observed by scanning electron microscopy (SEM), showing that the nanoparticles were evenly distributed and no obvious agglomeration was observed. The surface finish of the ceramic material after polishing was significantly improved, and the roughness was reduced to Ra = 0.1μm, which improved the aesthetics and surface quality of the material.
[0078] Embodiment 3,
[0079] Step 301: Select nano-SiC particles with a particle size of 40 nm and a specific surface area of about 150 m 2 / g. The surface of nano-SiC is nitrided by CVD method, and silane nitride (SiH4) is used to react at 1000°C to form a silicon nitride coating.
[0080] Step 302, weigh 20g of the surface-modified nano-SiC particles in Example 301, disperse them in 1000mL of ethanol, and add an appropriate amount of surfactant PVP. Place the prepared dispersion solution in an ultrasonic disperser and disperse it using ultrasound with a frequency of 40kHz. The dispersion time is 60 minutes. After the dispersion treatment, the dispersion is centrifuged at 4000rpm for 15 minutes, and the supernatant after centrifugation is dried at 70°C to obtain nanomaterial powder;
[0081] Step 303, preliminarily crush the blocky or large-particle ceramic matrix material ZrO2, and use a ball mill to control its particle size within the range of 2-5 μm. Screening uses 200 mesh (75 μm) and 325 mesh (45 μm) sieves to classify the powder. The screened ceramic matrix material needs to be homogenized by a mechanical mixer to ensure the uniformity of particle distribution. The speed of the mechanical mixer is set at 250 rpm, and the mixing time is 50 minutes.
[0082] Step 304, weigh the modified nano material nano alumina and the pretreated ceramic matrix material alumina, and add them in a ratio of 1:7, that is, 20 grams of nano alumina and 140 grams of zirconium oxide. Add ethanol as a dispersion medium, and the amount of ethanol added is 4 times the mass of the ceramic matrix material, that is, 560 grams. Pour the prepared mixed slurry into the ball mill of the planetary ball mill, and add 360 grams of zirconium oxide balls as grinding media. Set the speed of the ball mill to 600rpm and the mixing time to 4 hours. Remove the liquid part by spray drying or vacuum freeze drying to obtain a solid composite powder. During the drying process, control the temperature at 70°C.
[0083] Step 305, select a cemented carbide mold. The inner wall of the mold is coated with a boron nitride coating release agent. A small amount of pre-pressure of 10MPa is applied during the filling process. The hot pressing pressure is 20Mpa, the temperature is 1300°C, and the holding time is set to 50 minutes. The heating rate is set to 15°C / minute. After the holding is completed, the temperature is slowly cooled to room temperature, and the cooling rate is controlled at 10°C / minute.
[0084] Step 306: After cooling to room temperature, the sintered ceramic material is polished using diamond polishing paste by gradually reducing the sandpaper particle size until the surface reaches the desired smoothness.
[0085] The modified nano-SiC was observed through a transmission electron microscope (TEM) and the coating thickness was uniform, about 3nm. Through differential scanning calorimetry (DSC) testing, the modified SiC particles showed better stability at high temperatures, and the thermal expansion coefficient was reduced by 12%. The dispersibility in the ceramic matrix was improved by 28%. The flexural strength of the zirconium oxide (ZrO2) composite material reinforced with nano-silicon carbide (SiC) reached 520MPa, which is 25% higher than that of traditional ceramic materials. By applying a high-hardness nano-coating (such as SiC) on the surface of the ceramic material and performing subsequent polishing, the wear resistance and corrosion resistance of the material have been significantly improved. In the experiment, the ceramic material coated with the SiC layer showed a 20% improvement in wear resistance, making it perform better in harsh operating environments.
[0086] The same or similar parts between the embodiments in this specification can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the method embodiment described later, since it corresponds to the system, the description is relatively simple, and the relevant parts can be referred to the partial description of the system embodiment.
[0087] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A ceramic reinforcement process based on nanomaterials and a method for preparing nanomaterial-reinforced ceramics, characterized in that: include: Step 1: Select suitable nanomaterials and perform surface modification on them to improve their dispersibility; The surface of nanomaterials is modified by CVD process: the nanomaterials are placed in a CVD furnace and heated within a certain temperature range under certain protective atmosphere and modifier conditions to obtain modified nanomaterials; Step 2: Weigh an appropriate amount of the surface-modified nanomaterial in step 1, disperse it in a corresponding solvent, and add an appropriate amount of a surfactant to obtain a dispersion. The dispersed solution is placed in an ultrasonic disperser for ultrasonic dispersion treatment. After the ultrasonic dispersion treatment, the dispersed solution is further subjected to centrifugal treatment, and the supernatant after centrifugation is dried to obtain nanomaterial powder; Step 3, pretreatment of ceramic matrix materials. The pretreatment process includes crushing, screening, and homogenization by a mechanical mixer to ensure uniform particle size distribution of the pretreated material. The pretreatment operation is performed by preliminarily crushing the block or large particles of ceramic matrix materials and controlling the particle size within a certain range using a ball mill or grinder. After the pretreatment operation is completed, ceramic matrix material particles / powder with uniform particle size are obtained; Step 4: wet mixing the nano material powder obtained in step 2 and the ceramic matrix material particles / powder with uniform particle size obtained in step 3 in a liquid medium to obtain a mixed slurry, which is then ball milled in a ball mill to make the nano material evenly distributed in the ceramic matrix powder, and then the obtained mixture is further dried to obtain a composite ceramic powder; Step 5: Select an appropriate hot pressing mold to press the composite ceramic powder obtained in step 4 into a blank in a hot pressing process to obtain a hot pressed ceramic blank. The inner wall of the hot pressing mold needs to be precisely machined and coated with a release agent (such as graphite or boron nitride coating) to reduce friction and adhesion during the forming process, thereby ensuring the surface quality of the ceramic blank and smooth demolding; Step 6: Place the ceramic body obtained in step 5 in a sintering furnace for sintering. After sintering, slowly cool down to obtain nano-material reinforced ceramic. During the cooling process, the protective atmosphere is maintained to ensure that the ceramic material does not undergo oxidation reaction during the cooling process.
2. The nanomaterial-based ceramic reinforcement process and nanomaterial-reinforced ceramic preparation method according to claim 1, characterized in that: The nanomaterials in step 1 include but are not limited to one or more of nano boron nitride (BN), nano zirconium oxide (ZrO2) and nano silicon carbide (SiC), the protective atmosphere includes but is not limited to nitrogen and hydrogen; the modifier includes but is not limited to one or more of aminosilane, aminoethylsulfonate, and silicon nitride. The certain temperature range refers to 700-1000°C, which is selected according to the nanomaterial used.
3. The nanomaterial-based ceramic reinforcement process and nanomaterial-reinforced ceramic preparation method according to claim 1, characterized in that: The dispersion solution described in step 2 is prepared by dispersing 10-20 grams of nanomaterial in 200-1000 mL of deionized water or ethanol solution, selecting a solvent according to the chemical properties of the nanomaterial, and adding a surfactant at a concentration of 0.5-2% of the mass of the nanomaterial to obtain a dispersion solution.
4. The nanomaterial-based ceramic reinforcement process and nanomaterial-reinforced ceramic preparation method according to claim 1, characterized in that: The ultrasonic dispersion treatment method described in step 2 is specifically operated by using 20-40kHz ultrasonic waves for dispersion, and the dispersion time is controlled to be 30-60 minutes. The centrifugal technique described in step 2 is specifically operated by centrifuging at 3000-5000rpm in a centrifuge for 10-15 minutes. The drying technique described in step 2 is specifically operated by controlling the temperature at 60-80°C.
5. The ceramic matrix material pretreatment method according to step 3 of claim 1, characterized in that: The ceramic matrix material described in step 3 of claim 1 includes, but is not limited to, one or more of alumina and zirconia. The crushing operation in the pretreatment process described in step 3 is implemented by using a ball mill to process the ceramic matrix material, and controlling the particle size of the ceramic matrix material after ball milling to be between 2-5 microns. The screening operation described in step 3 is implemented by using 200 mesh and 325 mesh sieves to classify the ceramic matrix material powder obtained after the crushing operation, and taking the ceramic matrix material powder between 200 mesh (75μm) and 325 mesh (45μm). The homogenization processing parameters described in step 3 are specifically that the speed of the mechanical mixer is set between 100-300rpm, and the mixing time is 30-60 minutes.
6. The wet mixing process according to step 4 of claim 1, characterized in that: The mixed slurry described in step 4 is prepared by mixing the modified nanomaterial in step 2 and the pretreated ceramic matrix material in step 3 in a mass ratio of 1:9-1:4, adding ethanol as a dispersion medium, and controlling the liquid-to-solid ratio between 3:1 and 5:
1.
7. The grinding operation described in step 4 is specifically as follows: the amount of grinding media added is controlled to be 50-70% of the solid mass; the ball mill speed is set to 400-600rpm, and the mixing time is controlled to be 2-4 hours. The ceramic slurry drying treatment method described in step 4 adopts spray drying or freeze drying technology.
8. The hot pressing forming process according to step 5 of claim 1, characterized in that: The hot pressing mold in step 5 uses a hard alloy mold, and the inner wall is coated with a release agent. Further, the hot pressing operation pressure range is set to 20-50MPa, the temperature range is 1200-1600°C, the holding time is set to 30-60 minutes, and the heating rate is usually set to 10-20°C / min.
9. The post-sintering treatment process according to step 6 of claim 1, characterized in that: The cooling operation described in step 6 is to cool the temperature to room temperature by natural heat dissipation and then end the cooling. The protective atmosphere described in step 6 includes but is not limited to argon, nitrogen, etc.
Citation Information
Patent Citations
Preparation method of boron nitride nanotube-intensified silicon oxide ceramic
CN101817675A
Boron nitride nanosheet-reinforced ceramic-based composite material and preparation method thereof
CN106747530A
Preparation method of surface modified silicon carbide crystal whisker toughening reaction sintered silicon carbide ceramic
CN110304933A
Method for preparing monocrystalline silicon carbide nanofiber / silicon carbide ceramic-based composite material through nano-impregnation transient eutectic
CN114751760A
High-toughness composite nano ceramic material and preparation method thereof
CN115572164A